Prohibition of Torture - Hassanová, Rebecca Lilla (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter examines the prohibition of torture and other forms of ill-treatment as a foundational norm of international human rights law. The text interprets the ban on torture within its jus cogens character and erga omnes obligations, emphasising that it is non-derogable and applicable irrespective of treaty consent. The analysis clarifies the conceptual contours of torture and its differentiation from inhuman and degrading treatment, highlighting the interpretive space created by treaty language and the resulting central role of judicial and quasi-judicial bodies. The subchapters proceed through the main normative and institutional frameworks. Keywords: prohibition of torture, ill-treatment, jus cogens, inhuman treatment, degrading treatment